Dracocephalum heterophyllum (DH) Exhibits Potent Anti-Proliferative Effects on Autoreactive CD4+ T Cells and Ameliorates the Development of Experimental Autoimmune Uveitis - Bian, Jiang; Wang, Ke; Wang, Qilan; Wang, Pu; Wang, Ting; Shi, Weiyun; Ruan, Qingguo (Frontiers in Immunology, 2020)
Experimental autoimmune uveitis (EAU) is a CD4+ T cell mediated organ-specific autoimmune disease and has been considered as a model of human autoimmune uveitis. Dracocephalum heterophyllum (DH) is a Chinese herbal medicine used in treating hepatitis. DH suppressed the production of inflammatory cytokines through the recruitment of myeloid-derived suppressor cells (MDSCs) to the liver. However, it remains elusive whether DH can directly regulate CD4+ T cell biology and hence ameliorates the development of CD4+ T cell mediated autoimmune disease. In the current study, we found that DH extract significantly suppressed the production of pro-inflammatory cytokines by CD4+ T cells. Further study showed that DH didn’t affect the activation, differentiation, and apoptosis of CD4+ T cells. Instead, it significantly suppressed the proliferation of conventional CD4+ T cells both in vitro and in vivo. Mechanistic study showed that DH-treated CD4+ T cells were partially arrested at the G2/M phase of the cell cycle because of the enhanced inhibitory phosphorylation of Cdc2 (Tyr15). In addition, we demonstrated that treatment with DH significantly ameliorated EAU in mice through suppressing the proliferation of autoreactive antigen specific CD4+ T cells. Taken together, the current study indicates that DH-mediated suppression of CD4+ T cell proliferation may provide a promising therapeutic strategy for treating CD4+ T cell mediated diseases.